PSMA SPECT/CT with 99mTc-MIP-1404 in biochemical recurrence of prostate cancer: predictive factors and efficacy for the detection of PSMA-positive lesions at low and very-low PSA levels - Schmidkonz, Christian; Götz, Theresa; Kuwert, Torsten; Ritt, Philipp; Prante, Olaf; Bäuerle, Tobias; Goebell, Peter; Cordes, Michael (Annals of Nuclear Medicine, 2019)
Background: The in vivo expression of the prostate-specific membrane antigen (PSMA) can be investigated using the SPECT-suitable tracer 99mTc-MIP-1404. We investigated the performance of 99mTc-MIP-1404 PSMA SPECT/CT in the detection of PSMA-positive tumor lesions in patients suffering from biochemical recurrence of prostate cancer presenting with serum levels of the prostate-specific antigen (PSA) below 1 ng/mL. Methods: We retrospectively analyzed 99mTc-MIP-1404-SPECT/CT scans of 50 patients (25 with low PSA levels between > 0.5 and 1 ng/mL and 25 with very low PSA levels between 0.2 and 0.5 ng/mL) that had undergone whole-body planar scintigraphy and SPECT/CT of the thorax, abdomen and pelvis 3–4 h p.i. of 691 ± 72 MBq 99mTc-MIP-1404. All datasets were evaluated for the presence and location of PSMA-positive tumor lesions, in which maximal standardized uptake values (SUVmax) were also measured. Based on the results of the quantitative evaluation as well as on biochemical and histological parameters, predictive factors for a positive 99mTc-MIP-1404 scan result were determined. The influence of 99mTc-MIP-1404 PSMA SPECT/CT on further therapy planning was assessed, based on the decision-making of the interdisciplinary tumor board. Results: Pathological 99mTc-MIP-1404 uptake was detected in a total of 25 patients (50%). In the very low PSA subgroup, detection rates of PSMA-positive lesions suggestive of tumor recurrence were 44%, in the low-PSA subgroup 56%. Gleason scores ≥ 8 and the presence of antiandrogen deprivation therapy were further significant predictors of pathological 99mTc-MIP-1404 uptake. This was paralleled by significantly higher lesional SUVmax patients with PSA levels > 0.5 ng/mL and Gleason scores ≥ 8 compared to those without these two features. Changes in therapeutic strategy following MIP-1404 imaging were recommended by the interdisciplinary tumor board in 25/50 of patients. Conclusion: 99mTc-MIP-1404 PSMA-SPECT/CT demonstrated a high performance in detecting PSMA-positive lesions suggestive of tumor recurrence in patients with biochemical recurrence of prostate cancer and low and very low serum PSA levels. Results from MIP-1404 PSMA SPECT/CT have therapeutic impact in one-half of the patients examined by this technology.
CRIS-Team Scopus Importer:2019-10-29
Keywords: Low PSA levels; MIP-1404; Prostate cancer; PSMA; Quantitative SPECT/CT; SPECT/CT